Accessibility of the Integrated Educational Platform for pupils with special educational needs - Wojtyńska, Joanna (Virtualizing the lives of people with disabilities, 2021)
The pandemic limitation in the functioning of schools and the transition to distance learning increased the interest in the website www.epodreczniki.pl, where is located the so-called Integrated Educational Platform (ZPE). The article presents the genesis of ZPE, its content and, above all, the solution used to ensure the adaptation of the didactic materials on the above-mentioned side to the WCAG standard and the requirements of pupils with special educational needs (SEN). The adaptation of the materials was discussed in relation to the educational needs of students with various disabilities related to the use of ICT.